Safety and Efficacy of Reduced Dose of Enzalutamide in Patients with Castration-Resistant Prostate Cancer: A Systematic Review - Zineddine Belabaci; Lucas Mose; Omar El-Taji; Zina Otmani; Zein Alabdin Hannouneh; Issa Mohamad; Thomas Zilli; Osama Mohamad; Nadeem Pervez; Waleed Arafat; Ursula Vogl; Mohamed Shelan (Pharmaceuticals)
Objective: To review the efficacy and safety of reduced dose compared to standard dose Enzalutamide treatment for patients with castration-resistant prostate cancer (CRPC). Methods: PubMed, Scopus, Web of Science, and Cochrane databases were searched for randomized controlled trials and cohort studies reporting the use of Enzalutamide in reduced and standard doses in patients with castration-resistant prostate cancer. Searches were limited to articles published in the English language. Outcome assessments included progression-free survival (PFS), overall survival (OS), adverse events, and serum prostate-specific antigen (PSA) response. Results: Ten studies met the inclusion criteria, including 2481 patients treated with Enzalutamide. Seven studies were retrospective cohorts, two were prospective trials, and one was a prospective cohort. No consistent relationship was identified between OS and PFS and the Enzalutamide dosage. Reduced doses of Enzalutamide decreased the incidence of adverse events, particularly among elderly patients. Conclusions: This systematic review suggests that reduced doses of Enzalutamide in CRPC may maintain therapeutic efficacy in selected patients while improving tolerability. However, inconsistent findings and methodological limitations highlight the need for prospective randomized trials to define optimal and individualized dosing strategies.